2005
DOI: 10.1128/aem.71.7.3935-3941.2005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lateral-Flow Clostridium botulinum Neurotoxin Detection Kits for Food Analysis

Abstract: The suitability and sensitivity of two in vitro lateral-flow assays for detecting Clostridium botulinum neurotoxins (BoNTs) in an assortment of foods were evaluated. Toxin extraction and preparation methods for various liquid, solid, and high-fat-content foods were developed. The lateral-flow assays, one developed by the Naval Medical Research Center (Silver Spring, MD) and the other by Alexeter Technologies (Gaithersburg, MD), are based on the immunodetection of BoNT types A, B, and E. The assays were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 35 publications
1
62
0
4
Order By: Relevance
“…These lateral-flow devices (LFDs) have been used in the diagnosis of diseases caused by bacteria, fungi, toxins, and viruses, including HIV (9)(10)(11)(12)(13). We have previously reported on the successful incorporation of an Aspergillus-specific murine monoclonal antibody (MAb) into an LFD.…”
mentioning
confidence: 99%
“…These lateral-flow devices (LFDs) have been used in the diagnosis of diseases caused by bacteria, fungi, toxins, and viruses, including HIV (9)(10)(11)(12)(13). We have previously reported on the successful incorporation of an Aspergillus-specific murine monoclonal antibody (MAb) into an LFD.…”
mentioning
confidence: 99%
“…The assay is able to detect up to one unit dose of one mouse lethal dose (1 MLD), which is equivalent to approximately 10 pg/ml of neurotoxins (Sharma et al, 2005). Hence, this method is categorized quite sensitive.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore it takes special skills, animal ethics concerns, as well as the specificity of neurotoxins detected is still very limited. It also needs quite long time to get results, which is about 4 days or more (Sharma et al, 2005). Consequently several methods have been developed ranging from ELISA (Dezfulian et al, 1984;Witcome et al, 1999), immunoaffinity chromatographic column test (Gessler et al, 2005), fluorogenic assay (Anne et al, 2001), up to the bio-molecular test such as PCR (Fach et al, 1995;Braconnier et al, 2001;Kimura et al, 2001;Lindstrom et al, 2001;Fach et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several LFAs for the detection of different BoNT serotypes have been developed with detection limits usually between 0.3 and 250 ng/mL (Chiao et al 2004(Chiao et al , 2008aKlewitz et al 2006;Attrée et al 2007;Han et al 2007). Sharma and co-workers evaluated two commercial products on spiked food samples and found detection limits of above 20 ng/mL for BoNT complexes of serotypes A, B, and E (Sharma et al 2005). Others reported that some commercial tests were unable to recognize the purified holotoxin but detected the toxin complexes only (Gessler et al 2007).…”
Section: Rapid Detection Tools Based On Elisa Formatsmentioning
confidence: 99%